As tecnologias digitais da informação e comunicação na docência universitária nos cursos de administração e ciências contábeis - VESPASIANO, Luce Mary (2016)
The aim of this study is to investigate what they say teachers Administration courses and Accounting regarding the participation of digital technologies of information and communication in university teaching. For this, we carried out a study on the scientific and technological paradigms and their influences on knowledge of the professor and the educational context. It also addresses the importance of university professor knowledge envisaging the development of pedagogical and digital competence for the integration of Digital Technologies of Information and Communication (TDIC) in teaching and learning from the totality of vision, that is, transcending the fragmentary knowledge , technicist and reductionist observed in the current paradigm. The perspective used for the integration of TDIC in university teaching has theoretical support theoretical scheme entitled Pedagogical-Technological Knowledge Content (TPACK) Mishra & Koehler (2006). The authors state that, so there is the effective integration in teaching and learning, the teacher must have a body of technological knowledge, pedagogical and content, that is, requires the understanding that these phenomena occur in an articulated manner and not in isolation . Authors such as Shulman (1986, 1987) Mishra & Koehler (2006), Marcelo Garcia (2013), Morin (2008), Capra (1982), Moraes (2012), Behrens (2007), Masetto (2012), Pimenta and Anastasiou (2005), Cunha (2009), Freire (1987), Santos (2008), Le Boterf (2006), among others, are also part of the theoretical framework of the investigation. The study is characterized by a mixed approach. The participants were 47 university teachers of an institution of Minas Gerais and São Paulo. Data were collected through a structured questionnaire and interview and analyzed using the multidimensional statistical method made possible by software CHIC - Hierarchical Classification, Implicative and Cohesive - generating similarity trees it was possible to establish the relationship between the teachers surveyed and the variables the study and also the content analysis from the perspective of Bardin (1977). The analyzes show that the higher placed in search educational institutions have good infrastructure and promote teacher training courses. Most teachers already investigated attended courses TDIC, however, research suggests that these factors are not enough to promote the integration of TDIC in teaching and learning. Research also shows that teachers are still bringing TDIC to the classroom with technical bias, focusing on education and not in the teaching given in its full extent, as theoretical studies suggest for a better exploitation of the potential of TDIC. Another result indicated by the analysis is that teachers, in general, recognize the importance and potential of TDIC in the educational context and reframing of traditional teaching methods, promoting a more interactive environment, flexible, nice, dynamic and motivating and can strengthen the formal and informal communication in the teacher-student relationship, even with the possibility of improving student performance. The research has brought evidence that teach and develop pedagogical and digital competence for the integration of TDIC in teaching and learning to meet the twenty-first century demand is a complex task that requires the teacher to create the corpus of technological knowledge, pedagogical and articulated content to the entire vision. Thus, research has brought evidence that the knowledge of the university professor is still limited also by implications of paradigms and because of difficulties related to teacher training for the profession.